BUSTAMAN, A CULTURAL URBAN KAMPONG BASED ON CULINARY GULE AS RESPONSE TO URBAN CHANGES - Budi Sudarwanto; Gagoek Hardiman; Agung Budi Sardjono (Diponegoro University, 2019)
This research aims to deepen the culture of urban kampong. The concept of knowledge of Bustaman peoples in making needs to survive and adapt. This research used is grounded theory which kind of qualitative paradigm. The research procedure is empirical-inductive research process. Urban kampong is a burden in development activities. The character of urban spaces shows a chaotic and complex environment. There is a learning process by its citizens associated with the resilience of the kampong. It has a meaning related to culture of people and the physical environment. That kampong shows all the things about urban kampong problems. The culture of kampong shows defensive and adaptation. Bustaman kampong is widely known as gule village. The finding of a local knowledge concept are about how the people to sustain of their daily live. First, it was defined as the culture of citizens working hard to survive. The second is an effort to build social capital to adapt. The third is characterizes of kampong that has openness and friendly. Bustaman have been mention as a kininanti cage.